2014
DOI: 10.1161/circinterventions.113.000964
|View full text |Cite
|
Sign up to set email alerts
|

Optimization in Stent Implantation by Manual Thrombus Aspiration in ST-Segment–Elevation Myocardial Infarction

Abstract: Background-Manual thrombus aspiration (TA) is effective to reduce the thrombus burden during primary percutaneous coronary intervention for ST-elevation myocardial infarction. The objective of this study is to assess the impact of manual TA on stent implantation during primary percutaneous coronary intervention. Methods and Results-Population of the EXAMINATION trial (n=1498) was divided into 2 groups according to the use of TA. Immediate angiographic results, primary patient-oriented end point (combination of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

3
16
0
1

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 39 publications
3
16
0
1
Order By: Relevance
“…Erlinge et al recently documented with near‐infrared spectroscopy (NIRS) that TA—beyond thrombus—reduces culprit lesion lipid content by 28% in patients with ACS, thereby removing material that may embolize during stenting, and seems particularly useful if a large lipid core is present at the culprit site . Our results confirm and extend such knowledge, showing that TA adequately prepares culprit lesion before S‐PCI, as in the Everolimus‐eluting stent versus bare‐metal stent in ST‐segment elevation myocardial infarction (EXAMINATION) trial, where TA was associated with a higher rate of direct stenting and with the use of larger and fewer stents in comparison with conventional primary PCI. Here again, in the TOTAL trial an OCT substudy will be conducted to investigate the impact of thrombus removal and optical coherence tomography (OCT)‐guided PCI optimization on stent deployment .…”
Section: Discussionsupporting
confidence: 81%
“…Erlinge et al recently documented with near‐infrared spectroscopy (NIRS) that TA—beyond thrombus—reduces culprit lesion lipid content by 28% in patients with ACS, thereby removing material that may embolize during stenting, and seems particularly useful if a large lipid core is present at the culprit site . Our results confirm and extend such knowledge, showing that TA adequately prepares culprit lesion before S‐PCI, as in the Everolimus‐eluting stent versus bare‐metal stent in ST‐segment elevation myocardial infarction (EXAMINATION) trial, where TA was associated with a higher rate of direct stenting and with the use of larger and fewer stents in comparison with conventional primary PCI. Here again, in the TOTAL trial an OCT substudy will be conducted to investigate the impact of thrombus removal and optical coherence tomography (OCT)‐guided PCI optimization on stent deployment .…”
Section: Discussionsupporting
confidence: 81%
“…Recently, observational data from 1498 patients with STEMI that was identified in a randomized trial of treatment with drug-eluting stents showed that clinical outcomes with thrombus aspiration were similar to those with stenting alone. 19 Several meta-analyses of randomized trials of thrombus aspiration have had inconsistent results with respect to mortality and other clinical outcomes. 5,12,14 The findings of these meta-analyses are dominated by the results of TAPAS and the TASTE trial.…”
Section: Discussionmentioning
confidence: 99%
“…Initially it was associated with decreased mortality in randomized trials and meta‐analyses . More recently, larger trials , meta‐analyses , and large registries with over 27,000 patients have found no improvement in clinical endpoints with CTA. As a consequence, updated STEMI guidelines downgraded routine CTA in STEMI from a Class IIa recommendation to a Class III recommendation .…”
Section: Discussionmentioning
confidence: 99%